Management of Endometriomas - Muzii, Ludovico; Tucci, Chiara Di; Feliciantonio, Mara Di; Galati, Giulia; Verrelli, Ludovica; Donato, Violante Di; Marchetti, Claudia; Panici, Pierluigi Benedetti (Seminars in Reproductive Medicine, 2017)
Ovarian endometriomas affect 17 to 44% of women with endometriosis, and are often associated with pelvic pain and infertility. Treatment options include expectant management, medical and/or surgical treatment, and in vitro fertilization and embryo transfer (IVF-ET). The choice of treatment depends mostly on the associated symptoms. In most cases, surgery is the preferred choice, since endometriomas do not respond to medical treatment, which may only treat associated pain. In case of infertility, IVF-ET may be a suitable alternative to surgery, particularly when there is no associated pain. According to the best available scientific evidence, laparoscopic excision of the endometrioma wall should be considered the procedure of choice. Concerns have been raised as to the possibility that surgical excision may damage the ovarian reserve, but recent evidences demonstrate that part of the damage may be due to the presence of the endometrioma itself. Indication to surgical treatment should balance the possible risks of damaging the ovarian reserve with the advantages of surgery in terms of satisfactory pain relief rates and pregnancy rates, and of obtaining tissue specimen for ruling out the rare cases of unexpected ovarian malignancy. A score system to guide the clinician in the decision to perform or withhold surgery is presented.
Keywords: endometrioma; laparoscopy; medical treatment; ovarian reserve; surgical treatment